Simple Test Weak-Form Efficient Market Hypothesis on the Warsaw Stock Exchange - Sekuła, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper aims to determine whether the Polish capital market is efficient at low level. The test results suggest the presence of autocorrelation of daily returns on WIG index. However, observations showed weakening of the autocorrelation with the development of the Warsaw Stock Exchange.